Factors associated with poisoning by cleaning products in children: integrative review (Research, Society and Development, 2022)
Poisonings are the main accidents that occur with children, mainly to the public aged 0 to 4 years, to the detriment of the child's motor development process and due to the lack of knowledge of those responsible in relation to prevention methods and the absence of supervision, which directly or indirectly influences the incidence of cases. The objective is to understand what are the factors associated with childhood intoxication by cleaning products and to emphasize the importance of awareness and health education actions. This is an integrative literature review carried out through the VHL, LILACS, MEDLINE and PUBMED databases. Sixty-nine studies were found, and after evaluation, six were selected for the final sample. It was observed that cases of childhood intoxication by cleaning products are related to the early stages of the child's life and development. It is concluded that adequate storage is one of the factors that contribute to the reduction of cases of exogenous intoxication by products for domestic use and that health education actions are essential to minimize the occurrence of cases.